Delay discounting, demand, and social media usage Instagram (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
Problematic use of social media can be explained by the Theory of Reinforcer Pathology (TRP) and the Behavioral Perspective Model (BPM). TRP focuses on patterns such as high delay discounting rates and low demand elasticity, while BPM considers utilitarian and informational consequences. This study examined whether intense Instagram use is associated with steeper discounting for informational reinforcers (likes) and lower demand elasticity. Sixty-five university students participated by completing questionnaires on discounting, demand, and Instagram use, in a counterbalanced within-subject design. Results showed higher discounting for likes compared to money and lower demand elasticity among more dependent users. Trait effects (correlation between reinforcers) and magnitude effects (greater discounting in impulsive choices) were observed. The average number of likes correlated with discounting, suggesting that direct behavioral measures may be more sensitive to identifying problematic social media use patterns.Parte superior do formulário
Keywords: Problematic social media use; Delay discounting; Demand; Impulsivity; Self-control